Estrategias para minimizar la accidentalidad de los estudiantes de danza, en la Corporación Universitaria Cenda (2025)
Within the Cenda University Corporation, the dance and choreographic direction program is offered, whose objective is, through the body and movement, reflection and artistic creation, to contribute to the field of art and contemporary society. In the professional study of the different dance techniques, accidents occur that can cause negative consequences in the physical integrity of the student, affecting their training process temporarily or permanently; For these reasons, it is vitally important to have preventive strategies to minimize the causes of accidents within the Institution. Based on the priority risk management activities in Occupational Health and Safety (SST), we seek to provide a timely and pertinent solution through an adequate design of strategies to reduce risks in work environments. This is why this document presents a proposal based on educational campaigns, designed with the purpose of preventing and reducing accidents that affect students within the institution under study, based on the bases of SST, which arise as a result of a diagnostic process carried out at the Institution.